An adaptive median filter for the removal of periodic interference from an image - Weeks, Arthur R.; Kasparis, Takis; Keif, Brian (My University, 1994)
© 1994 COPYRIGHT SPIE. A typical method of removing a periodic interference from an image is to two-dimensional fast Fourier transform (FFT) the interference corrupted image and manually locate and remove the impulses due to the interference. The last step is to inverse fast Fourier transform the interference free spectrum to yield the restored image. This is a manual process usually requiring human interaction and several iterations. In this paper, an adaptive median filter applied to an interference corrupted spectrum is presented to automatically remove only the interference spectral components while leaving the spectral components of the interference free image unmodified. The result is an interference free image obtained automatically.